Modeling and implementation of a biomimetic robotic fish - Korkmaz, D.; Budak, U.; Bal, C.; Ozmen Koca, G.; Akpolat, Z.H. (My University, 2012)
In this study, design and implementation of a remote-controlled, 4-joints flapping mechanism and autonomous-swimming biomimetic robotic fish are presented. The propulsive model of the robotic fish is given considering the biological fish structure. The motion control of the robotic fish is performed by using speed and position control. The forward speed of the robotic fish can be adjusted by changing oscillation frequency, oscillation amplitude and length of the oscillation mechanism. Its position is controlled by implementing different joints angles. © 2012 IEEE.
21st International Symposium on Power Electronics, Electrical Drives, Automation and Motion, SPEEDAM 2012 -- 20 June 2012 through 22 June 2012 -- Sorrento -- 92961
Keywords: Autonomous swimming; Biomimetic Robotic fish; Carangiform motion; Propulsive model